Grade-Span Configuration - Theodore Coladarci; Julie Hancock (Journal of Research in Rural Education, 2002)
The author review the limited evidence regardingg grade-span configuration effects on academic achievement and other outcomes. A small group of studies, where researchers attempted to accoubt for confounding variables, report positive effects for less fragmented grade spans (e.g.. grades k-8 vs. 6-8). The meaning and implications of these results are discussed.